HUBUNGAN CORPORATE SOCIAL PERFORMANCE DAN KINERJA KEUANGAN PERUSAHAAN (Studi Empiris pada Perusahaan yang Menerbitkan Sustainability Report Sesuai Standar GRI) - Rahma, Candri; Syafruddin, Muchamad (Diponegoro Journal of Accounting, 2015)
The aims of this research are to know : (1) The influence of Corporate Social Performance to Corporate Finance Performance (2) The influence of Corporate Finance Performance to Corporate Social Performance. This research sample is annual report and sustainability report from companies that listed in ISRA 2012. The sampling method that used in this research is purposive sampling. There are 30 companies observed in 2012 which fulfilling criteria as this research sample. The analysis method of this research is simple regression analysis and multivariate regression analysis. The result of research show that Corporate Social Performance didn’t have a significant relation with Corporate Finance Performance. But on the other side, Corporate Finance Performance highly correlated to the Corporate Social Performance.